Association between HDACs and pro-inflammatory cytokine gene expressions in obesity. (4th July 2022) - Shanaki, Mehrnoosh; Omidifar, Abolfazl; Shabani, Parisa; Toolabi, Karamollah
Abstract: Histone deacetylases (HDACs) are important players in a variety of physiological and pathological conditions. Few studies have addressed HDAC expressions in human adipose tissue in obese individuals, and their association with pro-inflammatory cytokines. Here, we compared 20 non-obese and 20 obese women to investigate possible changes in gene expressions of HDAC2, 4, 5, and 6 in the subcutaneous adipose tissues (SAT) and visceral adipose tissues (VAT) of these individuals. Our findings showed decreased HDAC5 expression in SAT and elevated HDAC4 expression in VAT from the obese group compared with the non-obese group. Our analyses showed negative correlations between HDAC2, 5, and 6 and the obesity indices and positive correlations between HDAC4 and obesity indices. HDAC2 showed a positive correlation with pro-inflammatory cytokines whereas HDAC4, 5, and 6 were negatively correlated with pro-inflammatory cytokines. Our findings provide new evidence that implicates the important roles of HDACs in obesity and obesity-associated inflammation.